Curcumin-Induced Global Profiling of Transcriptomes in Small Cell Lung Cancer Cells - Mo, Fei; Xiao, Yinan; Zeng, Hao; Fan, Dian; Song, Jinen; Liu, Xiaobei; Luo, Meng; Ma, Xuelei (Frontiers in Cell and Developmental Biology, 2021)
Background: Curcumin, one of the promising candidates for supplementary therapy in cancer treatment, has been demonstrated by numerous preclinical and clinical evidence to be beneficial in treating various cancers. Apart from the tight association with the development of a deluge of pathological processes, the changes of some mRNAs and microRNAs(miRNAs) have been involved in the complicated anti-tumor activity. Therefore, our research focused on the role of curcumin in small cell lung cancer (SCLC) cells and drew a comprehensive transcriptomes profile by high throughput sequencing to understand the molecular mechanism of curcumin as an anti-tumor agent. Method：First, the apoptosis rate of H446 cells (a human SCLC cell line) was determined by the treatment of curcumin and the high output sequencing uncovered the altered expression profile of genes and miRNAs. KEGG analysis selected the potential signal pathway highly associated with the antiproliferative property of curcumin. Finally, the significantly changed miRNAs were verified and their regulated role in cell apoptosis was further examined. Result：The apoptosis rate of H446 cells increased under the elevated concentration of curcumin treatment. Besides, the significant downregulation of cell cycle-related genes was found in the curcumin-treated cells. Besides, a high level of miRNA-548 was found to play a negative role in the anticarcinogenic activity of curcumin. Conclusion：Our findings not only enriched the understanding of anti-tumor activity initiated by curcumin through figuring out the downregulated cell cycle-related pathways but also shed light on the novel therapeutic application of curcumin.